Influence of reinforcement viscous properties on reliability of existing structures strengthened with externally bonded composites. (15th September 2018) - Berardi, V.P.; Feo, L.; Mancusi, G.; De Piano, M.
Abstract: The time-depending stress transfer in existing structures strengthened with externally bonded fiber reinforced polymer (FRP) systems, due to viscous effects of reinforcement, is analysed in this paper. A new modelling strategy for assessing the long-term response of these composite beams was developed, by assembling two one-dimensional components (existing structural element and external strengthening) and accounting for thin-walled sectional geometry of FRPs. Several numerical experiments dealing with FRP laminates-reinforced concrete (RC) composite beams were performed and the corresponding results were compared with the predictions of the Effective Modulus Method (EM). A relevant stress redistribution between the components of the examined strengthened structures was observed.